Test of lepton universality with B0 - K*0е+е - decays; Journal of High Energy Physics; Vol. 2017 - Aaij R. Roel; Adeva B. Bernardo; Adinolfi M.; Ajaltouni Z. J. Zeina; Vagner A. R. Aleksandr Rudolfovich (2017, 2017)
Title screen